2020
DOI: 10.1002/mp.14416
|View full text |Cite
|
Sign up to set email alerts
|

Error detection and classification in patient‐specific IMRT QA with dual neural networks

Abstract: Purpose: Despite being the standard metric in patient-specific quality assurance (QA) for intensitymodulated radiotherapy (IMRT), gamma analysis has two shortcomings: (a) it lacks sensitivity to small but clinically relevant errors (b) it does not provide efficient means to classify the error sources. The purpose of this work is to propose a dual neural network method to achieve simultaneous error detection and classification in patient-specific IMRT QA. Methods: For a pair of dose distributions, we extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…For example, positioning errors (i.e., MLC errors, EPID misalignment), can be clearly reflected in contrast maps or DTA maps. 34 In this work, the measured PD images were directly compared to the calculated PD images for difference map calculation, accounting for the existing discrepancy between the PDIPmodeled images and acquired PD images. The obtained results in the current work further proved the feasibility of such error detection methods in clinical environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, positioning errors (i.e., MLC errors, EPID misalignment), can be clearly reflected in contrast maps or DTA maps. 34 In this work, the measured PD images were directly compared to the calculated PD images for difference map calculation, accounting for the existing discrepancy between the PDIPmodeled images and acquired PD images. The obtained results in the current work further proved the feasibility of such error detection methods in clinical environments.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing to the DD‐DTA‐blended gamma maps, the four difference maps could reflect different errors patterns resulted from various beam delivery errors separately hence more informative features could be preserved. For example, positioning errors (i.e., MLC errors, EPID misalignment), can be clearly reflected in contrast maps or DTA maps 34 . In this work, the measured PD images were directly compared to the calculated PD images for difference map calculation, accounting for the existing discrepancy between the PDIP‐modeled images and acquired PD images.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have proposed machine learning‐based dose analysis in static beam IMRT QA dosimetry. Potter et al analyzed DTA maps and DD histograms obtained using the approach of a 2‐D diode array with two types of deep learning 29 . They performed error simulation for MLC mispositioning, MLC transmission factor, MU, source size, and misalignment of measuring device.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, error detection models that focus on errors other than MLC leaf positioning errors have also been investigated. [29][30][31][32] For static beam IMRT QA dosimetry, Potter et al developed an error detection model using a deep learning approach to detect errors of MLC position, MLC transmission, MU, effective source size, and alignment of a measuring device. Sakai et al reported a machine learning approach focusing on MLC modeling error detection, such as dosimetric leaf gap (DLG).…”
Section: Introductionmentioning
confidence: 99%
“…Convolutional neural networks (CNNs) can effectively perform image-related tasks by analyzing images at different scales using convolutional layers to extract useful information and generate final outputs (31). Accordingly, a number of researchers have proposed CNN-based patient-specific dose verification using dose maps as the CNN input (32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%